A brief group cognitive behavior therapy for undergraduate migrant students’ academic anxiety : a pilot study - Stefany Valentia,; Menaldi, Adhityawarman (Penerbit Universiti Kebangsaan Malaysia, 2022)
Academic anxiety is one of the most common problems experienced by undergraduate migrant students, because of the various challenges they encounter in their studying place. Cognitive behavioral group intervention is found to be effective in treating academic anxiety. To explore the feasibility of a brief cognitive behavior group therapy focused on reducing academic anxiety in Indonesian undergraduate migrant students, a pre–post quasi-experimental design was used. A total of 6 participants (mean age= 19.3 years, SD= 0.52) who scored above 40 in The Student Worry Questionnaire were chosen. The Intervention was conducted in a total of 5 sessions, 2.5 hours long each. An individual follow-up interview was conducted two weeks after the last session. Friedman’s ANOVA indicated a non-significant difference (χ₂ = 3.217, p = .241) between pre-test (Mean rank = 2.33), post-test (mean rank = 2.25), and follow up (mean rank = 1.42). However, a post-hoc pairwise comparison showed a large effect size. Descriptively, the academic concerns subscale of 5 participants decreased from post-test to follow-up. Qualitative analysis showed that participants gained benefit from the CBT group intervention. Findings support the feasibility, preliminary efficacy and efficiency of those five weekly session interventions when applied to a sample of Indonesian migrant students.